2020
DOI: 10.3390/coatings10111028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on the Structural, Magnetic, Surface Energy and Optical Properties of Co32Fe30W38 Films Deposited by Direct-Current Magnetron Sputtering

Abstract: In this study, a 10–50 nm Co32Fe30W38 alloy thin film sputtered on glass substrates was annealed at different temperatures for 1 h including room temperature (RT), 300, 350, and 400 °C. The structure, magnetic properties, surface energy, and optical properties of the Co32Fe30W38 alloy were studied. X-ray diffraction (XRD) patterns of the as-deposited Co32Fe30W38 thin films showed the amorphous structure. The apparent body-centered cubic (BCC) CoFe (110) structure was exhibited after 300 °C annealing for 1 h. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Figure 1a-c demonstrates that the intensity of CoFe (110) peaks increased as the post-annealing temperature increased. According to [23], it was suggested that the crystallization of as-deposited CoFeW films on Si(100) substrate was better than ones on glass substrate.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1a-c demonstrates that the intensity of CoFe (110) peaks increased as the post-annealing temperature increased. According to [23], it was suggested that the crystallization of as-deposited CoFeW films on Si(100) substrate was better than ones on glass substrate.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…The various thicknesses (t f ) of as-deposited and annealed CoFeW films and, therefore, the effect of crystallinity on the magnetic properties of CoFeW films were also studied. In our previous research, the as-deposited and post-annealing glass/CoFeW were examined for their magnetic and crystallinity properties, as mentioned in Table 1 [23]. In this study, it was found that the thermal stability of Co 40 Fe 40 W 20 was about 350 • C. However, in order to apply a magnetic film in MRAM, the 400 • C of thermal tolerance is required for complementary metal-oxide-semiconductor (CMOS) and back-end-of-line (BEOL) process compatibility [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the work is investigating surface roughness in order to study the relationship between surface energy and magnetic-optical properties in CoFeSm thin films of various thicknesses and annealed at different temperatures. Moreover, the outcome of the present study is compared with the magnetic and adhesive characteristics of Cobalt Iron Vanadium (CoFeV), Cobalt Iron Tungsten (CoFeW), and Cobalt Iron Ytterbium (CoFeYb), and Cobalt Iron Yttrium (CoFeY) in Table 1 [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 contains the abbreviations and full names of the proper nouns. In earlier studies, the magnetic and adhesion characteristics of CoFeY materials were compared to those of Cobalt Iron Vanadium (CoFeV), Cobalt Iron Tungsten (CoFeW), and Cobalt Iron Ytterbium (CoFeYb) in Table 2 [ 23 , 24 , 25 , 26 , 27 ]. In contrast to previous CoFeY films that were sputtered on Si(100) substrates to study magnetic and adhesion outcomes, the goal of this research is to produce thin films on glass substrates and also investigate optical transmittance properties.…”
Section: Introductionmentioning
confidence: 99%